Research on distributionally robust optimization method considering the flexibility of power grids along CZ railway - Jiawei Liu; Min Li; Jing Gou; Wenhao Sun; Qiao Zhang; Zhigang Liu (Energy Reports, 2023)
To avoid the problem of insufficient flexibility of the power grid along the cz railway due to source-load fluctuations, a distributionally robust optimization method considering flexibility is proposed in this paper. Firstly, Wasserstein distance is used to establish the uncertainty set of flexibility demand caused by source-load fluctuation, and a risk-cost model of insufficient flexibility is constructed to couple to the objective function. Combined with the flexibility chance constraint, the flexibility over-limit probability is limited to a certain confidence level in the fuzzy set, and a distributionally robust chance constraint optimization model based on Wasserstein distance is established. Then, the proposed model is transformed into a linear programming problem to be solved by dual theory and inner approximation transformation. Finally, a simulation study of the power grid along the CZ railway is carried out to verify the correctness and effectiveness of the model. The experimental results show that the proposed method can improve the flexibility capacity of the system without sacrificing economy.